2016
DOI: 10.1021/acsami.6b08676
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Boosts Charge Separation for High Solar-Driven Photocatalytic Performance

Abstract: Bandgap engineering of photocatalysts is a common approach to achieving high effective utilization of solar resource. However, the difficulty in achieving bandgap narrowing and high activity simultaneously seems to be irreconcilable via the traditional modification pathway. Herein, we have substituted iodine for a fraction of bromine atoms in BiOBr to overcome this restriction and provided some deep-seated insights into how the substitution boosts the photocatalytic properties. The substituted BiOBr 0.75 I 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…[23,24] d) Facet-controlled fabrication; [25][26][27] It has been demonstrated that exposed {0 01}f acets could enhance the thermodynamic stabilitya nd photogenerated electron-hole pairs separation efficiency of BiOCl. [26] f) Solid solution of BiOCl x Br 1Àx , [28][29][30][31] BiOBr x I 1Àx , [32,33] andB iOCl x I 1Àx . [22,34,35] The BiOBr x I y solid solution exhibits an arrow band gap and promotes the diffusion of electrons and inhibition of photogenerated electrons and hole recombination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] d) Facet-controlled fabrication; [25][26][27] It has been demonstrated that exposed {0 01}f acets could enhance the thermodynamic stabilitya nd photogenerated electron-hole pairs separation efficiency of BiOCl. [26] f) Solid solution of BiOCl x Br 1Àx , [28][29][30][31] BiOBr x I 1Àx , [32,33] andB iOCl x I 1Àx . [22,34,35] The BiOBr x I y solid solution exhibits an arrow band gap and promotes the diffusion of electrons and inhibition of photogenerated electrons and hole recombination.…”
Section: Introductionmentioning
confidence: 99%
“…f) Solid solution of BiOCl x Br 1− x , BiOBr x I 1− x , and BiOCl x I 1− x . The BiOBr x I y solid solution exhibits a narrow band gap and promotes the diffusion of electrons and inhibition of photogenerated electrons and hole recombination . e) Crystal defect structure; The crystal defects can be considered as active sites, which not only enhance the adsorption capacity but also narrow the band gap for photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…57,58 The τ 1 , τ 2 , and τ 3 of CN-MA400m are all longer than those of CN (Figure 5d), and the prolonged τ 1 is ascribed to the generated single nitrogen vacancies in the bulk of CN-MA400m, while the prolonged τ 2 may result from the formed surface vacancy clusters. 57,59,60 The I 1 − I 3 reflect the relative concentrations of vacancies or defects. The I 3 of both CN and CN-MA400m approaches zero, suggesting few large voids in the samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among them, Nd and C are the carrier density and interface capacitance, e0 is the amount of charge carried by an electron, ε is the dielectric constant, ε0 is vacuum permittivity and, V is the applied voltage [45]. According to calculations, the carrier densities of BiVO4, CV-x (x=1~4) and CdS are 2.92×10 23 , 7.08×10 24 , 9.64×10 24 , 1.55×10 25 and 9.46×10 23 and 6.04×10 24 cm -3 , respectively.…”
Section: Electrochemical Performancesmentioning
confidence: 99%